Multiple Mucous Retention Cysts (Mucocele) of the Oral Mucosa: A Case Report - Gholamreza Jahanshahi; Amir Mansour Shirani; Faezeh Khozeimeh (Wolters Kluwer Medknow Publications, 2007)
To our knowledge, the occurrence of multiple mucoceles is not very common. This case report presents a 62-year-old man with multiple nodules on the upper and lower labial mucosa as well as both buccal mucosae with unknown history. Histopathology evaluation showed minor salivary gland ducts dilated to the point of cyst formation. The cysts seemed to be formed either as a result of dilatation of salivary ducts due to altered secretion or because of an acquired or congenital weakness in the ductal structure. The physiopathology of these findings is discussed.